The Relationship Between Pre-Koas Program and Clinical Registration Outcomes in Students of The Faculty of Medical YARSI University Class of 2016 - Salsa Nabila Rianti Putri; Miranti Pusparini (Junior Medical Journal, 2023)
Medical education is passed through two stages, namely the academic stage and the clinical clerkship stage. Before entering the professional stage, the university provides debriefing which aims to make students more prepared to carry out their clinical stages which will end with a test that aims to c proceed to the next stage, namely the profession stage. After completing and fulfilling the requirements, graduates get a diploma with a Doctor's degree. In previous studies, it was found that there was a significant correlation between GPA scores and UKMPPD scores. From the results of this study, it was found that there was evidence that the preparatory process for an activity affected the final score of an activity and the purpose of this study was to find out whether the results of pre-coach training affected the results of clinical clerkships. The research method uses Cross Sectional. The research sample was students of the Faculty of Medicine, YARSI University class of 2016. Data collection used a questionnaire. The results of the Pre Koas debriefing scores showed that most of the students got C grades of 19 people (22.4%), CD scores of 17 people (20%), and at least B- and B+ scores of 1 person (1.2%) and results of clinical clerkship scores Most of the students got 65 A- grades (76.5%), 17 AB students (20%) and 3 A's (3.5%). In the results of bivariate analysis, there was no relationship between pre-coach training and clinical clerkship results.